2 - Understanding the Political Economy of Contemporary Africa - Amin, Samir (Africa Development, 2021)
Current academic programmes in social sciences for African Universities have been prescribed by the World Bank and allied authorities in order to destroy any capacity to develop critical thought. Unable to understand really existing systems which govern the contemporary world, the brain washed cadres are reduced to the status of ‘executives’ implementing programmes decided elsewhere, unable to contribute to changing that world rejected by their own people. A critique of this totalitarian shallow ‘unique thought’ which has invested the teaching of economics is the subject of this paper. Further readings, offering a critique of ‘post modernist’ sociology and cultu- ral studies (see, for instance, Samir Amin, The Liberal Virus, Pluto 2004, pages 19 et seq.) complete the picture of the ongoing intellectual disaster. CODESRIA constitutes an important intellectual locus conducting real open debates with a strong sense of responsibility.